Wear of Farm Buildings in Selected Farms (Agricultural Engineering, 2016)
The objective of the article was to compare the level and structure of wear and tear of various types of the most popular agricultural buildings in the selected agricultural farms. A comparative analysis of physical and functional wear as well as investment expenditures of the selected objects in 2010-2014 was carried out. The scope of the article covered agricultural buildings with which 90 farms in the southern Poland are equipped. These farms were varied on account of the surface area and the production nature. The detailed analysis covered: cowsheds, piggeries, garages, fruit and vegetable storages, greenhouses and barns. The average age of the majority of farm buildings as well as a considerable degree of physical wear in comparison to a lower functional wear was determined.